Elucidating the resistance to failure under tribological tests of various boron-based films by XPS and ToF-SIMS - Spadaro, F.; Rossi, A.; Lainé, E.; Woodward, P.; Spencer, N.D. (Applied surface science, 2017)
[Display omitted] •Boron-based thermal films were grown in the presence of ZnDTP.•Thermal films and glasses were characterized by ToF-SIMS.•Effects of tribological tests on ball-disc sliding pairs were determined.•Mechanisms for both tribochemical and tribomechanical reactions have been proposed.•The failure mode of boron-free thermal films was explained. Tribotests performed on boron-based thermal films have revealed higher mechanical durability and lower wear coefficients compared to results from tests performed on boron-free thermal films. In the current study, in order to follow and identify the tribochemical reactions taking place in the contact regions, post-characterization has been carried out on the steel ball and on the steel disc. The techniques adopted to achieve this goal were small-area X-ray photoelectron spectroscopy (XPS) and time-of-flight secondary-ion mass spectroscopy (ToF-SIMS). The contact areas have been investigated before and after failure of the thermal films, revealing thermal-film removal inside the wear track on the disc and the presence of a transfer film in the contact area on the steel ball following tribotesting. Furthermore, borate contributions in the deeper layers within the tribo-stressed area on the disc were revealed at the end of the tribotest. These procedures shed light on the tribomechanical and tribochemical reactions taking place in the contact region, on the ability of boron species to sustain tribological stress and provide mechanical stability, and on the mechanical-mixing processes occurring within the sliding contacts. The mass spectra collected before tribotesting on all thermal films suggest the presence of phosphate- and borate-containing structures.